Exploring Financial Behavior: A Qualitative Investigation into Psychological Factors Influencing Risk Preferences and Investment Decisions - Suriyanti, S.; Mandung, Fitriani; Afiah, Nur; Irmayani, I. (Manunggal Halim Jaya, 2024)
This qualitative study investigates the psychological determinants influencing risk preferences and investment decisions. Grounded in phenomenology and interpretivism, the research aims to explore subjective experiences related to financial behavior. Employing purposive sampling, participants were selected based on diverse criteria. Data collection involved semi-structured interviews, participant observation, and document analysis. Thematic analysis revealed intricate interplays between personal experiences, cognitive biases, emotions, social influences, and financial literacy, shaping individuals' risk perceptions and decision-making processes. Findings underscore the multifaceted nature of financial behavior, highlighting the significance of personality traits, cognitive styles, and decision-making biases. Risk-averse individuals prioritized capital preservation, while sensation seekers pursued high-risk, high-reward investments. Moreover, individuals' self-efficacy influenced their investment strategies. Cognitive biases, such as overconfidence and loss aversion, further impacted investment decisions. The study emphasizes the importance of considering psychological factors in designing personalized financial interventions and educational programs. Future research directions include longitudinal studies, cross-cultural comparisons, and interdisciplinary approaches integrating insights from psychology, economics, and finance. This research contributes to the advancement of knowledge in behavioral finance and informs practical implications for financial advisors and policymakers, aiming to enhance individuals' financial well-being and decision-making competence.